Exploring the role of ubiquitination modifications in migraine headaches - Zhu, Qian; Yang, Jin; Shi, Lei; Zhang, Jieying; Zhang, Peng; Li, Junlong; Song, Xiaoli (Frontiers in Immunology, 2025)
Migraine is a complex neurovascular disorder whose pathogenesis involves activation of the trigeminal vascular system, central and peripheral sensitization, and neuroinflammation. Calcitonin gene-related peptide (CGRP) plays a dominant role and activation of MAPK and NF-κB signaling pathways regulates neuropeptide release, glial cell activation, and amplification of nociceptive signals. Aberrant activation of these pathways drives migraine onset and chronicity. The ubiquitin-proteasome system (UPS) is involved in neurological and inflammatory disorders. ubiquitination in the UPS is achieved through a cascade of enzymes, including Ub-activating enzyme (E1), Ub-coupling enzyme (E2), and Ub-ligase (E3). The aim of this review is to systematically explore the role of ubiquitination in the regulation of MAPK and NF-κB signaling pathways, with a focus on the mechanisms of ubiquitinating enzymes in neuroinflammation and pain signal amplification, and to explore their potential as diagnostics, biomarkers, predictors of response to therapy, and monitoring of chronicity in migraine disease.